Biochar application as a tool to decrease soil nitrogen losses (NH3 volatilization, N2O emissions, and N leaching) from croplands: Options and mitigation strength in a global perspective - Liu, Qi; Liu, Benjuan; Zhang, Yanhui; Hu, Tianlong; Lin, Zhibin; Liu, Gang; Wang, Xiaojie; Ma, Jing; Wang, Hui; Jin, Haiyang; Ambus, Per; Amonette, James E.; et al. (Global change biology, 2019)
Biochar application to croplands has been proposed as a potential strategy to decrease losses of soil‐reactive nitrogen (N) to the air and water. However, the extent and spatial variability of biochar function at the global level are still unclear. Using Random Forest regression modelling of machine learning based on data compiled from the literature, we mapped the impacts of different biochar types (derived from wood, straw, or manure), and their interactions with biochar application rates, soil properties, and environmental factors, on soil N losses (NH3 volatilization, N2O emissions, and N leaching) and crop productivity. The results show that a suitable distribution of biochar across global croplands (i.e., one application of <40 t ha−1 wood biochar for poorly buffered soils, such as those characterized by soil pH<5, organic carbon<1%, or clay>30%; and one application of <80 t ha−1 wood biochar, <40 t ha−1 straw biochar, or <10 t ha−1 manure biochar for other soils) could achieve an increase in global crop yields by 222–766 Tg yr−1 (4%–16% increase), a mitigation of cropland N2O emissions by 0.19–0.88 Tg N yr−1 (6%–30% decrease), a decline of cropland N leaching by 3.9–9.2 Tg N yr−1 (12%–29% decrease), but also a fluctuation of cropland NH3 volatilization by −1.9–4.7 Tg N yr−1 (−12%–31% change). The decreased sum of the three major reactive N losses amount to 1.7–9.4 Tg N yr−1, which corresponds to 3%–14% of the global cropland total N loss. Biochar generally has a larger potential for decreasing soil N losses but with less benefits to crop production in temperate regions than in tropical regions. Biochar is expected as a potential strategy for cropland N conservation. Uncertainties exist, however, regarding the extent and spatial variability of biochar function at the global level. Using Random Forest regression modelling of machine learning, this study mapped the impacts of different biochar types, and their interactions with biochar application rates, soil properties and environmental factors, on soil N losses (NH3 volatilization, N2O emissions, and N leaching) and crop productivity. Results show that a suitable biochar management has the potential to achieve a decrease in 3%–14% in global cropland N losses, with an increase in 4%–16% in global crop production.